Need Assessment of Women Dairy Farmers - Saroj Kumari , Nishi Sethi , Joginder Singh Malik and Vikram Yogi, (Indian Journal of Extension Education, 2015)
The present study was conducted in Hisar district of Haryana state. From Hisar district, two blocks Adampur and Hisar-Iwere selected randomly. From selected blocks, two villages, namely Siswal from Adampur and Dabra from Hisar-1 wereselected by random technique. From each selected village, 50 women were selected randomly, thus making a total sampleof 100 women. From selected villages, 20 women who were interested in training in dairy farming were selectedpurposively. Majority of the respondents belonged to middle age group, illiterate, married and belonged to joint family ofmedium family size. Eighty-four per cent respondents had no social participation and had small herd size. Most of therespondents (25%) had medium land holding and lived in pacca houses. Training need score was obtained highest for thetask housing management of cattle shed (Mean-76.83 and rank-I), followed by animal health, watering, wallowing andbathing, breeding, post-parturition care, bedding, care and management of calves, feeding, marketing, farm managementand accounting and milking and milk product preparation ranked from II to XI, respectively. Similarly, training need washigh for animal health (ranked-II) but dairy farm women had high knowledge (74.1) and low difficulty (2.19). It wassurprise to see that after computing frequency, importance, difficulty and knowledge of last ranks were given to farmmanagement and accounting (X rank) and milking and milk product preparation (XI rank) but highest learning difficultyby dairy farm women was perceived for these components. It was also interesting to note that negligible percentage ofrespondents performed tasks of dairy farm management and accounting and marketing where money matters wereinvolved.